Evaluation of low-chill requiring apple cultivars for juice production: juicing potential, sensory profile and phenolic composition - Stander, Jeanette Hermine (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.